Platelet refractoriness – practical approaches and ongoing dilemmas in patient management - Stanworth, Simon J.; Navarrete, Cristina; Estcourt, Lise; Marsh, Judith (British journal of haematology, 2015)
Summary Platelet refractoriness can represent a significant clinical problem that complicates the provision of platelet transfusions, is associated with adverse clinical outcomes and increases health care costs. Although it is most frequently due to non‐immune platelet consumption, immunological factors are also often involved. Human leucocyte antigen (HLA) alloimmunization is the most important immune cause. Despite the fact that systematic reviews of the clinical studies evaluating different techniques for selecting HLA compatible platelets have not been powered to demonstrate improved clinical outcomes, platelet refractoriness is currently managed by the provision of HLA‐matched or cross matched platelets. This review will address a practical approach to the diagnosis and management of platelet refractoriness while highlighting on‐going dilemmas and knowledge gaps.